Innovative Patient Involvement During Covid-19: Keeping Patients at the Heart of HTA - Rasburn, Mark; Crosbie, Helen; Tonkinson, Amanda; Chandler, David; Dhanji, Tasneem; Habgood, Stephen; O'Brien, Stella (Frontiers in Medical Technology, 2021)
The COVID-19 pandemic and lockdown measures in the United Kingdom resulted in significant challenges and created opportunities for innovation to keep patients at the heart of HTA. The introduction of the Coronavirus Act 2020 (UK Government, 2020a) and the associated public health guidance (UK Government, 2020b) meant that NICE’s conventional HTA methods were no longer feasible. NICE introduced rapid, innovative updates to patient and public involvement (PPI), decision-making meetings, and consultations to harness the expertise of patients and the public to ensure guidance addressed the expected concerns and identified barriers which could impact access. This article describes the PPI support for NICE’s rapid shift to virtual meetings and virtual engagement. We utilize the author’s experience and patient and public contributor feedback to understand the experience of participating in a virtual setting and identify four themes: accessibility; inclusivity; transparency; and intrapersonal relationships and committee dynamics. The article also considers how patient representatives participated in, and facilitated, the development of guidance for a hypothetical technology to keep patients and the public at the heart of expedited and novel HTA processes to identify and understand the expected patient concerns and potential barriers for when a technology would be introduced.